Cavernous artery intima‐media thickness predicts the response to sildenafil in erectile dysfunction patients as a morphological parameter. (20th June 2021) - Zhang, Yuyang; Zhou, Wang; Wu, Xu; Liu, Guodong; Dai, Yutian; Jiang, Hui; Zhang, Xiansheng
Abstract: While the intima‐media thickness (IMT) of the cavernous artery was used for diagnosis for vascular erectile dysfunction (ED) with more accuracy than the peak systolic velocity, the role of the IMT in predicting treatment responses remained unexamined. A total of 136 patients with ED were enrolled. The baseline clinical and laboratory characteristics were collected. Penile Doppler ultrasonography (PDU) was performed on all patients by a blinded sonographer. Sildenafil was administrated to all patients with an adjusted dose of 50 or 100 mg on demand over a period of 3 months. A follow‐up was conducted on all patients using the Erectile Hardness Score (EHS) questionnaire along with the visual and tactile version of the standardised EHS tool. The peak systolic velocity (PSV) and IMT were compared between sildenafil responders and sildenafil nonresponders, while receiver operator characteristic (ROC) curves were used to calculate the cut‐off values and compare the test power respectively. There was no statistical difference from the baseline characteristics. The IMT of cavernous artery was more accurate than PSV to predict the sildenafil response (AUC = 0.809, 0.626 respectively). IMT could predict sildenafil responders more accurately than PSV, and the cut‐off value of the IMT of the cavernous artery was less than 0.22 mm.